In Search for a Missing Part: Identificational and Generational Motivation in Learning the L2 - Jelaska, Zrinka (Array, 2005)
This paper deals with a special type of adult learners of minor, small or less widely taught languages who take language L2 courses. It addresses non-classroom L2 learners who have acquired the language they are learning in childhood and have a certain level of listening and spoken communicative competence but lack grammatical competence. Some spoke it as the only mother language in the early childhood, some acquired it bilingually, but before the mother language fully developed the second language achieved dominance and became their L1. Two aspects are analyzed. One is the learning process they have to go through in order to progress in the linguistic communicative competence, e.g. de-fossilization or de-automatization of their acquired knowledge. The other is their motivation. Many of them have double motivation. The external motivation includes respect, obedience, or homage to parent(s), grandparent(s) or other ancestors, relating to family history, curiosity, the wish to speak or find relatives, possible business partners etc. The internal motivation includes competition, wishes to please, to benefit, to understand one's life history, to integrate oneself better with the emigrant society. But often there is a deeply rooted search for identity, the quest for the lost family or personal language and culture that was interwoven with it, the urge to integrate parts of self that were abandoned or pushed away by themselves or family members. Although this type of motivation could be viewed as a special case of integrative motivation, the terms identificational and generational motivation will be proposed to account for two subtypes of affective factors: personal and parental. The paper will explore some cases where major struggles to break through the linguistic and psychological obstacles were followed by major steps in gaining linguistic communicative competence.